2009
DOI: 10.1002/mana.200610786
|View full text |Cite
|
Sign up to set email alerts
|

The structure of compact disjointness preserving operators on continuous functions

Abstract: The duals of C 0 (a, b) and C[a, b] with respect to disjointness preserving groups are characterized. A. Plessner's result (1929) about the translation group is extended. A Wiener-Young type theorem for disjointness preserving groups is obtained. It is assumed that the reader is familiar with the notions of a Banach lattice, positive operator and disjointness preserving operator. [AB], [LZ] and [MN] are good references for this material. We also assume familiarity with the theory of C 0-semigroups and groups. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
9
0

Year Published

2009
2009
2013
2013

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 14 publications
1
9
0
Order By: Relevance
“…Whenever A is an abelian C * -algebra, every irreducible finite type I von Neumann factor in A * * is isomorphic to C. Thus, the description of the weakly compact disjointness preserving linear operators between commutative C * -algebras obtained by Lin and Wong [27] follows now as consequence of our Theorem 8 (see also Remark 9).…”
Section: Remarkmentioning
confidence: 73%
See 3 more Smart Citations
“…Whenever A is an abelian C * -algebra, every irreducible finite type I von Neumann factor in A * * is isomorphic to C. Thus, the description of the weakly compact disjointness preserving linear operators between commutative C * -algebras obtained by Lin and Wong [27] follows now as consequence of our Theorem 8 (see also Remark 9).…”
Section: Remarkmentioning
confidence: 73%
“…Lin and Wong proved in [27,Theorem 2.6] that T being compact is equivalent to T being weakly compact. On the other hand, every compact operator between Banach spaces factorises compactly through some closed subspace of c 0 (compare [13, Exercise 6, (iii), Page 15]).…”
Section: Remarkmentioning
confidence: 99%
See 2 more Smart Citations
“…It was shown that a bounded disjointness preserving operator is a weighted composition operator. In the recent paper [9], a concrete representation is given for compact, weakly compact and completely continuous disjointness preserving operators from C 0 (X) into C 0 (Y ).…”
Section: Introductionmentioning
confidence: 99%